2012
DOI: 10.1093/annhyg/mes055
|View full text |Cite|
|
Sign up to set email alerts
|

Workplace Measurements by the US Occupational Safety and Health Administration since 1979: Descriptive Analysis and Potential Uses for Exposure Assessment

Abstract: IMIS and the CEHD datasets represent the biggest source of multi-industry exposure data in the USA and should be considered as a valuable source of information for occupational exposure assessment. The lack of empirical data on biases, adequate interpretation of non-detects in OSHA data, complicated by suspected differential under-reporting, remain the principal challenges to the valid estimation of average exposure conditions. We advocate additional comparisons between IMIS and CEHD data and discuss analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…The poor validity on both the four and two-category scales suggests that even a limited, a priori, characterization of exposure may help determine appropriate semi-quantitative categories for the exposure range and the number of exposure categories to use for expert assessment in a workplace or study before requesting experts to provide their exposure estimates. For example, syntheses of the data in the published literature 37-39 or from inspection measurements 40-44 and other exposure databases 45 can provide useful information on exposure variability and help anchor the experts’ ratings to a concentration scale.…”
Section: Discussionmentioning
confidence: 99%
“…The poor validity on both the four and two-category scales suggests that even a limited, a priori, characterization of exposure may help determine appropriate semi-quantitative categories for the exposure range and the number of exposure categories to use for expert assessment in a workplace or study before requesting experts to provide their exposure estimates. For example, syntheses of the data in the published literature 37-39 or from inspection measurements 40-44 and other exposure databases 45 can provide useful information on exposure variability and help anchor the experts’ ratings to a concentration scale.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the higher odds found in the findings could be due to the high probability that the chemical substance will cause harm under certain conditions of use when the chemical levels exceed the PEL [16]. Another reason accounting for the higher odds and disparity might be the susceptibility of the biological system of the participants in a susceptive environment (the ability of a chemical substance to elicit a toxic response) [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Peters et al [11] reported that the amount of missing information on the reasons for measurement collection (e.g., survey, inspection/complaints, compliance) varied across the five agents in the ExpoSYN database, ranging from 18% for PAH to 58% for asbestos. Statistical challenges occur when using laboratory sources of measurements, especially for analytes measured as part of a panel; these approaches will need to consider whether the non-detected samples represent ‘present but not quantified’ or ‘absent’ [50••]. Statistical challenges also occurred when combining individual measurements and exposure concentrations reported as summary measurements [36, 37, 38•, 39, 40, 41••] and when combining expert judgment with measurement data sources [5, 6, 24, 25••].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, comparisons of the COLCHIC and US OSHA IMIS inspection databases provided similar multi-industry portraits of formaldehyde exposure despite a potential for very different occupational settings [7]. A review of evaluations of US OSHA measurements found that no biases were consistently reported across studies or agents [50••]. However, comparisons of two sources of US OSHA measurements, an inspection database and a laboratory database, found only 39% of the lead measurements were reported in both databases [50••].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation